Unraveling the Role of Cu0 and Cu+ Sites in Cu/SiO2 Catalysts for Water‐Gas Shift Reaction. Issue 18 (26th August 2020) - Chen, Chongqi; Ren, Hongju; He, Yuanyuan; Zhan, Yingying; Au, Chaktong; Luo, Yu; Lin, Xingyi; Liang, Shijing; Jiang, Lilong
Abstract: CuOx /SiO2 precursor was successfully fabricated by an ammonia evaporation hydrothermal method. Upon reduction in 5 vol % H2 /N2 at 250, 300, 350, 400, or 450 °C, CuO and copper phyllosilicate species in the precursor bring about the formation of highly dispersed Cu 0 and Cu + species, respectively. The Cu + /Cu 0 ratios were studied by XAES technique, while the particle sizes were estimated on the basis of HRTEM images. It is disclosed that the ratios and particle sizes varied with CuOx /SiO2 reduction temperatures. The results of in situ DRIFTS and XAES characterization reveal that both Cu 0 and Cu + are active for CO adsorption and water dissociation, especially so with Cu 0 and Cu + particles of small sizes. It was also observed that the adsorption of CO on Cu + is stronger than that on Cu 0, and Cu 0 is more active than Cu + for water dissociation. Among the prepared Cu/SiO2 catalysts, the one resulted from precursor reduction at 300 °C shows the highest CO conversion in WGS reaction, which is attributed to the small size of Cu 0 (2.45 nm) and the large amount of Cu + . Abstract : Cu/SiO2 catalysts : Both Cu 0 and Cu + are active for CO adsorption and water dissociation. The CO adsorbed on Cu + is more stable than that on Cu 0, and Cu 0 is more active for water dissociation than Cu + .